Thermally stimulated self-healing capabilities of ZrB2-SiC ceramics. Issue 15 (December 2021) - Monteverde, F.; Saraga, F.; Reimer, T.; Sciti, D.
Abstract: The ultrahigh temperature ceramic-matrix composites (UHTCMCs) are the core class of innovative materials. One of the key-features that such a new class of materials should exhibit is self-repair of damage without any external intervention. In the present work, a set of ZrB2 -SiC ceramics (SiC from 5 to 15 vol.%) was produced by hot-pressing: besides SiC, also 5 vol.% Y2 O3 was added in the starting mixture to search for an improved self-healing capability (SH). Dedicated set-ups to thermally stimulate samples in severely oxidizing atmosphere up to 2278 K were designed and realized. To assess the SH capabilities, the retained flexural strengths were measured at room temperature using samples damaged by indentations and then heat treated from 1773 K to 2278 K. The strength recovery rates were measured and correlated to the SH efficiency.